1999
DOI: 10.1073/pnas.96.15.8745
|View full text |Cite
|
Sign up to set email alerts
|

Lithium activates the serine/threonine kinase Akt-1 and suppresses glutamate-induced inhibition of Akt-1 activity in neurons

Abstract: This report describes a modulatory action of lithium and glutamate on the activity of serine͞threonine kinase Akt-1. Lithium is most commonly used to treat bipolar disorder, but the mechanism of its therapeutic action remains unknown. We have recently demonstrated that lithium protects against glutamate-induced excitotoxicity in cultured brain neurons and in an animal model of cerebral ischemia. This study was undertaken to investigate the role of Akt-1, activated by the phosphatidylinositol 3-kinase (PI 3-K) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
364
4
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 504 publications
(393 citation statements)
references
References 35 publications
24
364
4
1
Order By: Relevance
“…Data concerning the antipsychotic drug action on these kinases are scarce. Interestingly, only mood stabilizers (lithium and valproate), which are also used in therapy of schizophrenia, are known to phosphorylate both Akt and GSK-3b (Chalecka-Franaszek and Chuang, 1999;De Sarno et al, 2002). In line with our finding, which showed that the 5-day presence of chlorpromazine and clozapine in culture medium increased the level of phospho-Akt in Neuro-2A cells, it has been reported that chronic treatment with haloperidol enhanced phosphorylation of Akt in the frontal cortex of mice (Emamian et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Data concerning the antipsychotic drug action on these kinases are scarce. Interestingly, only mood stabilizers (lithium and valproate), which are also used in therapy of schizophrenia, are known to phosphorylate both Akt and GSK-3b (Chalecka-Franaszek and Chuang, 1999;De Sarno et al, 2002). In line with our finding, which showed that the 5-day presence of chlorpromazine and clozapine in culture medium increased the level of phospho-Akt in Neuro-2A cells, it has been reported that chronic treatment with haloperidol enhanced phosphorylation of Akt in the frontal cortex of mice (Emamian et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Recently it was reported that PI 3-kinase activity is decreased in occipital cortex of suicide subjects (Hsiung et al, 2003) and that ECS (Altar et al, 2004) or long-term lithium treatment (Chalecka-Franaszek and Chuang, 1999) increases PI 3-kinase activity. Given the role of PI 3-kinase in a plethora of biological functions, these and our present findings appear to be quite significant and suggest the possibility that dysfunction of PI 3-kinase signaling may be important in the pathophysiologic mechanisms of suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that lithium elicits its neuroprotective/neurotrophic effects primarily through inhibition of GSK-3 (Gould et al, 2004;Liang and Chuang, 2007). Besides direct inhibition, lithium has been shown to indirectly inhibit GSK-3 through phosphorylation of GSK-3α at Ser21 and GSK-3β at Ser9 by multiple mechanisms including the activation of PKA (Jope, 1999a), phosphatidylinositol 3-kinase (PI3-K)-dependent AKT (Chalecka-Franaszek and Chuang, 1999), protein kinase C (PKC) (Kirshenboim et al, 2004), as well as the involvement of GSK-3 autoregulation Liang and Chuang, 2007). GSK-3 inhibition is also likely involved in the anti-depressant and anti-manic effects of lithium observed in rodent models (Gould et al, 2004;Kaidanovich-Beilin et al, 2004;O'Brien et al, 2004).…”
Section: Introductionmentioning
confidence: 99%